Response of microalgae to large-seaweed cultivation as revealed by particulate organic matter from an integrated aquaculture off Nan'ao Island, South China. (August 2018) - Zhang, Anhong; Wen, Xu; Yan, Hongyu; He, Xiufang; Su, Hong; Tang, Hongqu; Jordan, Richard W.; Wang, Yang; Jiang, Shijun
Abstract: Large seaweed cultivation has proven an effective means to inhibit harmful microalgae at experimental scales and battle eutrophication in Chinese coastal waters, but essentially there is a lack of field-scale studies to explore the underlying mechanism. Here we present a 1.5-year-long time series of particulate organic matter (POM) and settling particulate matter (SPM) concentrations from an integrated aquaculture of Gracilaria lemaneiformis off the coast of Nan'ao Island, South China from April 2014 to August 2015. The microscopic examination and geochemical characteristics show that the POM mainly consisted of microalgae. The mean POM concentration increased 99.8%, 71.2%, 45.8% and 111.9% at the four sampling sites during the non-cultivation period, while decreased 25.5%, 17.3%, 12.2% and 20.3%, respectively, during the seaweed cultivation period. These results suggest that the large scale seaweed cultivation can remove excess nutrients and inhibit microalgal growth, thereby contributing to the improvement of coastal marine aquaculture environment. Graphical abstract: Unlabelled Image Highlights: A 1.5-year-long particulate organic matter and settling particulate matter record Particulate organic matter (POM) mainly consists of microalgae. POM concentration decreases during large seaweed cultivation period. POM concentration increases when during non-seaweed cultivation period. Large seaweed cultivation helps improve coastal aquaculture environment.